The Chinese version of the cardiac depression scale: Mokken scaling - Watson Roger; Wang Wenru; Hare David L; Ski Chantal F; Thompson David R (Health and Quality of Life Outcomes, 2012)
Abstract Background Myocardial infarction is a major cause of death and morbidity in many countries, including China. The aim of this study was to analyse a Mandarin Chinese translation of the Cardiac Depression Scale for a hierarchy of items according to the criteria of Mokken scaling. Findings Data from 438 Chinese participants who completed the Chinese translation of the Cardiac Depression Scale were analysed using the Mokken scaling procedure and the 'R' statistical programme using the diagnostics available in these programmes. Correlations between Mandarin Chinese items and Chinese translations of the Hospital Anxiety and Depression Scale and the Beck Depression Inventory were also analysed. Fifteen items from the Mandarin Chinese Cardiac Depression Scale were retained in a weak but reliable Mokken scale; invariant item ordering was evident but of low accuracy and the Mokken scaled items of the Chinese Cardiac Depression Scale correlated with the Hospital Anxiety and Depression Scale and the Beck Depression Inventory. Conclusions Items from the Mandarin Chinese Cardiac Depression Scale form a Mokken scale and this offers further insight into how the items of the Cardiac Depression Scale relate to the measurement of depression in people with a myocardial infarction.